PENGARUH SERVANT LEADERSHIP, KOMUNIKASI INTERPERSONAL DAN KARAKTERISTIK INDIVIDU TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN - Onsardi Onsardi; Rano Febriyansah (Yayasan Insani Mandiri Santani, 2025)
This study aims to determine the influence of servant leadership, interpersonal communication, and individual characteristics on organizational commitment among employees of PT. Galempa Sejahtera Sejahtera Bersama (GSB) in the BLW Empat Lawang region. The type of research used is quantitative research with a descriptive approach. The data collection techniques used are observation, documentation, and questionnaires. The data analysis techniques used include descriptive analysis, inferential analysis using SPSS, and determination analysis.The results of this study indicate that servant leadership has a positive effect on organizational commitment. This means that the better the servant leadership, the higher the organizational commitment. Interpersonal communication has a positive and significant effect on organizational commitment. This means that the better the interpersonal communication, the higher the organizational commitment. Individual characteristics have a positive and significant effect on organizational commitment. This means that the better the individual characteristics, the higher the organizational commitment. Servant leadership, interpersonal communication, and individual characteristics simultaneously or collectively have a positive and significant impact on employee organizational commitment at PT. Galempa Sejahtera Bersama (GSB) in the BLW Empat Lawang region. This means that if the levels of servant leadership, interpersonal communication, and individual characteristics are good, they will enhance employee commitment. Keywords: Servant Leadership, Interpersonal Communication, Individual Characteristics, Organizational Commitment